The "experiment" in the history of economics - Fontaine, Philippe, 1960-; Leonard, Robert, 1962- (New York, NY : Routledge, 2005)
Annotation Testament to the variety of ways in which 'experimentation' has been important in the creation of economic knowledge, this wide-ranging collection of essays will interest those seeking to expand their historical understanding of the discipline.
Experimental economic games / Robert W. Dimand -- The allais paradox and its immediate consequences for expected utility theory / Sophie Jallais and Pierre-Charles Pradier -- Experimentation, general equilibrium, and games / S. Abu Turab Rizvi -- Thought- and performed experiments in Hayek and Morgenstern / Alessandro Innocenti and Carlo Zappia -- Social comptabilism and pure credit systems / Mauro Boianovsky and Guido Erreygers -- The vanity of rigour in economics / Nancy Cartwright.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Economics; Game theory; Electronic books